PENGARUH WORK-LIFE BALANCE DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA PEGAWAI KELURAHAN DI LINGKUNGAN KECAMATAN BUGUL KIDUL KOTA PASURUAN - Samsul Arifin; Nasharuddin Mas; Sodik (Bajang Institute, 2025)
The purpose of this study is to obtain empirical evidence of the influence of work-life balance and transformational leadership style on employee performance, both directly and through the mediation of organizational commitment.This study was quantitative and employed the SEM-PLS method. Data were obtained through questionnaires distributed to 60 village employees in the Bugul Kidul District, Pasuruan City.Five of the seven hypotheses tested showed significant effects. However, hypotheses three and six did not. Work-life balance did not improve employee performance, either directly or through the mediation of organizational commitment. Transformational leadership style, on the other hand, significantly influenced the performance of village employees in the Bugul Kidul District, Pasuruan City, both directly and through the mediation of organizational commitment.